Development and application of endothelium-targeted microparticles for molecular magnetic resonance imaging - Jefferson, A; Wijesurendra, R; McAteer, M; Choudhury, R (2012)
Molecular imaging of disease states can enhance diagnosis allowing for accurate and more effective treatment. By specifically targeting molecules differentially expressed in disease states, researchers and clinicians have a means of disease characterization at a cellular or tissue level. Targeted micron-sized particles of iron oxide (MPIO) have been used as molecule-specific contrast agents for use with magnetic resonance imaging (MRI), and early evidence suggests they may be suitable for use with other imaging modalities. Targeting of MPIO to markers of disease is commonly achieved through the covalent attachment of antibodies to the surface of the particles, providing an imaging agent that is both highly specific and which binds with high affinity. When comparing micron-sized particles with nanometre-sized particles, the former provide substantial signal dropout in MRI and confer the sensitivity to detect low levels of target. Furthermore, larger particles appear to bind to targets more potently than smaller particles. Animalmodels have also demonstrated favorable blood clearance characteristics of MPIO, which are important in achieving favorable signal over background and to attain clearance and disposal. Although the current generation of commercially available MPIO are not suitable for administration into humans, future work may focus on the development of biodegradable and nonimmunogenic MPIO that may allow the use of these imaging agents in a clinical setting. © 2012 Wiley Periodicals, Inc.